Model of sustainable utilization of organic solids waste in Cundinamarca, Colombia - Castañeda Torres, Solanyie; Rodriguez Miranda, Juan Pablo (Universidad y Salud, 2017)
Introduction: This article considers a proposal of a model of use of organic solids waste for the department of Cundinamarca, which responds to the need for a tool to support decision-making for the planning and management of organic solids waste. Objective: To perform an approximation of a conceptual technical and mathematician optimization model to support decision-making in order to minimize environmental impacts. Materials and methods: A descriptive study was applied due to the fact that some fundamental characteristics of the studied homogeneous phenomenon are presented and it is also considered to be quasi experimental. The calculation of the model for plants of the department is based on three axes (environmental, economic and social), that are present in the general equation of optimization. Results: A model of harnessing organic solids waste in the techniques of biological treatment of composting aerobic and worm cultivation is obtained, optimizing the system with the emissions savings of greenhouse gases spread into the atmosphere, and in the reduction of the overall cost of final disposal of organic solids waste in sanitary landfill. Based on the economic principle of utility that determines the environmental feasibility and sustainability in the plants of harnessing organic solids waste to the department, organic fertilizers such as compost and humus capture carbon and nitrogen that reduce the tons of CO2.